ASSISTING FOREIGN LANGUAGE USING 外语课 FOREIGN LANGUAGES MODULE FOR STUDENTS OF NURUL ISLAM ISLAMIC BOARDING SCHOOL - Alip Nuryanto; Acep Muwahid; Muhammad Hifdil Islam (Najah: Journal of Research and Community Service, 2023)
One of the activities of students that needs to be developed is their knowledge. Apart from religious knowledge, today's students are required to keep up with current developments, one of which is learning foreign languages. The aim of providing foreign language assistance is to hone the potential of Nurul Islam female students in foreign languages. In Laweyan village there is the Nurul Islam Islamic boarding school. This boarding school is included in the comprehensive boarding school, which has 23 female students. The accompanying method used is the ABCD (Asset Based Community Development) method. The result of mentoring Nurul Islam female students is that Nurul Islam female students can understand how to pronounce and write foreign language vocabulary, especially English and Mandarin. And Nurul Islam students can develop and improve foreign languages ​​into modern languages.